Pengaruh pemberian tepung biji durian sebagai subtitusi jagung dalam pakan ayam petelur terhadap rasio heterofil-limfosit dan produksi telur - Khoirun Nissa; Fajar Wahyono; Nyoman Suthama (Faculty of Animal Science, Universitas Brawijaya, 2019)
The aim of this study was to determine the effect of feeding durian seed flour as corn substitution on heterophyl/lymphocyte (H/L) ratio and hen day production (HDP). Experimental animals were 120 birds of laying hens allocated into for 4 treatments with 5 repications. Treatments applied were T0= without durian seed flour (control); T1= 3% durian seed flour to substitute corn; T2= 6% durian seed flour to substitute corn; and T3: 9% of durian seed flour to substitute corn. The parameters observed were serum glutamate oksaloasetate transaminase (SGOT), H / L ratio and hen day production (HDP). Data were analyzed using analysis of varian sand continued to Duncan's multiple range test if the treatments showed the significant effect. The results showed that the treatment with durian seed flour at the level of 9% (T3) was significant (P <0.05) on SGOT, H/L ratio, and HDP. In conclusion, durian seed flour at the level of 9% resultsincreases SGOT, H / L ratio,and a decreases HDP.